Allometrical correlation of biacromial and bicristal breadth to height growth in 7-15 years old children in Bantul Regency Yogyakarta Province - Janatin Hastuti, Janatin Hastuti (Universitas Gadjah Mada, 2004)
Background: Changes in body measurements during growth period cause change in their proportion, and this relationship can be measured using allometrical method. Growth of biacromial and bicristal in children are specific, because they can indicate the sexual dimorfism between boys and girls. Objective: The aims of this studi are to know the relationship between growth of biacromial and bicristal breadth to growth of height in 7-15 years old boys and girls in Bantul Regency, Yogyakarta Province. Methods: Investigation was conducted in 284 children of 7 up to 15 years old which consist of 136 boys and 148 girls. The samples were divided into 9 groups and were measured on height, biacromial and bicristal breadth. The datas were analysed using allometrical method expressed by an exponential regression equation. Student-t analysis was use to determine the difference of each measurement between boys and girls at the same age.Result: The result showed that biacromial breadth grew faster proportionally to height in 7 up to 11 and 13 up to 15 year old boys, and on the 7, 8, and 10 up to 15 years old girls. Bicristal breadth grew faster proportionally to height for all groups of age. Biacromial breadth grew faster proportionally to bicristal breadth th 8 up to 9 and 13 up to 15 year old boys and 7 year old girls. Girls of 8 up to 15 years old grew slower on biacromial breadth compared to bicristal growth.Conclusions: The conclusion was biacromial and bicristal breadth grew faster proportionally to height of boys and girls for almost all of age. Biacromial breadh of boys grew faster than bicristal breadth. In contrast, biacromial breadth of girls in the same age grew slower than bicristal breadth.Key words: growth-stature-biacromial breadth-bicristal breadth-allometrical method